Pipeline rules of thumb handbook : a manual of quick, accurate solutions to everyday pipeline engineering problems - McAllister, E. W. (Gulf Professional, 2013)
Presented in easy-to-use, step-by-step order, this book is a quick reference for day-to-day pipeline operations. For more than 35 years, this book has served as the "go-to" reference for solving even the most day-to-day vexing pipeline workflow problems. Now in its Eighth Edition, this handbook continues to set the standard by which all other piping books are judged. Along with over 30% new or updated material regarding codes, construction processes, and equipment, this book continues to offer hundreds of "how-to" methods and handy formulas for pipeline construction, design, and engineering and features a multitude of calculations to assist in problem solving, directly applying the rules and equations for specific design and operating conditions to illustrate correct application, all in one convenient reference